Conceptual ecology and invasion biology reciprocal approaches to nature - Cadotte Marc William; Fukami Tadashi; McMahon Sean M (Netherlands Springer, 2006)
In this edited volume, global experts in ecology and evolutionary biology explore how theories in ecology elucidate the invasion processes while also examining how specific invasions informs ecological theory. The chapters in this volume utilize many of
Keywords: Biological invasions; Ecology